Diversidade em Modulação Aplicada a Canais de Comunicações Móveis: Efeito dos Erros de Estimação de Canal na Transmissão de Imagens - Lopes, Waslon Terllizzie A.; Madeiro, Francisco; Galdino, Juraci F.; Aguiar Neto, Benedito G.; Alencar, Marcelo Sampaio (Journal of Communication and Information Systems, 2017)
In the present paper the modulation diversity (MD) technique is applied to image transmission (based on vector quantization) over a Rayleigh fading channel. The benefits of MD are presented and discussed. The combination of MD with the index assignment technique (robust vector quantization) is evaluated. The work also evaluates the effects of channel estimation errors on the performance of a communication system that uses MD, in terms of bit error rate and quality of the reconstructed images.